2015
DOI: 10.1002/jmv.24166
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus aggravates the ox-LDL-induced apoptosis of human endothelial cells via promoting p53 signaling

Abstract: Oxidized low-density lipoprotein (ox-LDL) is well recognized to play a key role in the development of atherosclerosis. And influenza virus infection has been also recognized to promote the atherosclerosis onset and progressing. However, little is known about the mechanism into it. In present study, we investigated the infection of A/Porto Rico/8/1934 (H1N1) (PR8) influenza virus in human endothelial Eahy926 cells, and determined the induction of apoptosis by the virus infection in the cell. Then we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…A previous study demonstrated that influenza virus aggravates the ox-LDL-induced apoptosis of human endothelial cells by promoting p53 signaling (35). Infection with A/Porto Rico/8/1934 (H1N1) (PR8) influenza virus in human endothelial EA.hy926 cells induced apoptosis, which was aggravated by ox-LDL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that influenza virus aggravates the ox-LDL-induced apoptosis of human endothelial cells by promoting p53 signaling (35). Infection with A/Porto Rico/8/1934 (H1N1) (PR8) influenza virus in human endothelial EA.hy926 cells induced apoptosis, which was aggravated by ox-LDL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Both influenza and ox-LDL have been shown to increase apoptosis in vascular endothelial cells, the latter through caspase-9 and caspase-3 cascades (87-91). One study has shown that influenza virus infection synergistically increases ox-LDL-induced apoptosis when compared to apoptosis caused by influenza or ox-LDL alone (97). These influenza-induced effects are possible mechanisms involved in atherosclerotic progression ( Figure 1).…”
Section: Direct Effect Of Influenza On Atherosclerosismentioning
confidence: 99%
“…Thus, the permanent status of endothelial activation promoted by these comorbidities would aggravate endothelial dysfunction caused by a viral inflammatory response and could be responsible for the most prevalent fatal outcome described in these patients. 48 Suo and colleagues 49 showed that H1N1pdm09 is responsible for potentiating endothelial cell apoptosis in patients who already have atherosclerosis. In this context, SARS-CoV-2 infection of the pneumocytes, besides having an essential role in the inflammatory activation/dysfunction of endothelial cells, would also lead to endothelial cell death, causing the discontinuity of the alveolar-capillary barrier and facilitating the movement of the virus from the alveolar septum through the alveolar-capillary lumen.…”
Section: Discussionmentioning
confidence: 99%